Lowpass and Bandpass Filter Designs Based on DGS with Complementary Split Ring Resonators - Omair, Ghofran E. Al-; Mahmoud, Samir F.; Zayed, Ayman S. Al- (Applied Computational Electromagnetics Society Journal (ACES), 2022)
We present novel designs of compact lowpass filters (LPF) and bandpass filters (BPF) based on defected ground structures (DGS) using two complementary split ring resonators (CSRR) that are etched in the ground plane. The geometries of the two CSRRs, of unequal areas, are optimized for a LPF with sharp cutoff and wide stop band. For the design of the BPF, a gap capacitor is added in series with the main transmission line and the two or three etched CSRRs are designed to achieve a given bandwidth, and a wide rejection band. Simulation results on the SEMCAD-X software are compared with circuit models and measurements on fabricated lowpass and bandpass filters.